More Scottish than British the 2011 Scottish Parliament election - Carman, Christopher J. 1969-; Johns, Robert 1975-; Mitchell, James 1960- (The comparative territorial politics series, 2014)
"With the aid of the most extensive and comprehensive survey data extracted from voters during the 2011 Scottish General, this book analyses the reasons behind why the SNP not only retained their mandate from the people to govern Scotland but further succeeded in winning a resounding majority in the Scottish Parliament. In tackling this overarching question other complex issues are also explored such as whether a pre-occupation with events at Westminster confined the Scottish Elections to the realm of 'second-order' elections? What impact the financial crisis had on elected a parliament that in reality has little economic power? The volume also has a broader appeal to devolved parliamentary elections more broadly by exploring what matters to voters when they cast their ballots for their national parliament in a complex, multi-level Political system. Examining performance evaluations, party loyalties and constitutional preferences, the authors show that Scottish elections are increasingly Scottish affairs, where voters are concerned with government competence - in domestic matters and in managing relations with Westminster. "..